PENGARUH PRICE DISCOUNT DAN BONUS PACK TERHADAP KEPUTUSAN PEMBELIAN PADA MEREK MOBIL SUZUKI (Studi Kasus: Masyarakat Kota Padang) - Afrida, Afrida (Sekolah Tinggi Ilmu Ekonomi Riau, 2021)
This study aims to determine (1) the effect of price discount on purchasing decisions on the Suzuki car brand, the case study of the Padang City Community, (2) the effect of the bonus pack on purchasing decisions on the Suzuki car brand, the Padang City Community case study, (3) the effect of price discount and bonuses. pack on purchasing decisions on the Suzuki car brand, the case study of the Padang City Community, (4) the magnitude of the influence of price discount and bonus pack on purchasing decisions on the Suzuki car brand, the Padang City Community case study. This type of research is quantitative research. The population in this study is the people of Padang City with a total sample of 96 people. Sample selection was done randomly using a questionnaire method which was analyzed using multiple linear regression analysis with the help of SPSS which included t test, F test, and coefficient of determination. The results showed that; (1) the price discount has a positive and significant effect on purchasing decisions on the Suzuki car brand, the case study of the Padang City Community, it is shown from the value of t count = 4.234 > t table = 1.661 or p-value = 0.000 < a = 0.05, ( 2) the bonus pack has a positive and significant effect on purchasing decisions on the Suzuki car brand, the Padang City Community Case study, it is shown from the t count = 4.621 > t table = 1.661 or p-value = 0.000 < a = 0.05, (3 ) price discount and bonus pack have a joint effect on purchasing decisions on the Suzuki car brand, the case study of the Padang City Community, it is shown from the calculated F value = 62,063 > F table = 3.09 or p-value = 0.000 < a = 0.05. The magnitude of the influence of price discounts and bonus packs on purchasing decisions on the Suzuki car brand in the case study of the Padang City Community is 57.2%, it is shown from the analysis value of the coefficient of determination, which is 0.572 or 57.2%.